Detection of RF unsafe devices using a parallel transmission MR system. Issue 5 (30th November 2012) - Graesslin, Ingmar; Krueger, Sascha; Vernickel, Peter; Achtzehn, Johannes; Nehrke, Kay; Weiss, Steffen
<x xml:space="preserve">Abstract</x> Purpose The permanent presence of devices (pacemakers) inside a patient, or the need to use other devices (catheters), for diagnosis and treatment, usually represents a contraindication for a magnetic resonance examination. To help overcome this problem, a novel and noninvasive magnetic resonance system‐based concept is proposed to detect potentially unsafe radio frequency (RF) conditions of such devices to ensure patient safety. Methods This concept makes use of parallel transmit technology by monitoring currents in individual RF transmit coil elements during RF transmission using suitable current sensors. For interventional devices, current changes can be directly measured, whereas for implanted devices, the use of reference signals is proposed, which cannot be measured in the patient. Results Coupling of unsafe devices to transmit coils led to detectable current changes in the elements because of energy absorption into the device. The concept was successfully tested on interventional and implantable devices and turned out to be so sensitive that even very weak RF coupling to these devices was detectable. Conclusion In this study, basic feasibility to detect RF unsafe conditions was successfully demonstrated. In the future, RF patient safety may be improved in the presence of implanted devices, as well as during interventions using this concept. Magn Reson Med 70:1440–1449, 2013. © 2012 Wiley Periodicals, Inc.